Thick multilayer polyimide film and manufacturing method thereof
Patent Information
- Application Number
- JP2023546538
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2022-01-26
- Filing Date
- 2022-01-27
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2042-01-27
AI Technical Summary
【0014】 本発明は、高厚度ポリイミドユニットフィルム、これを含む多層ポリイミドフィルムおよびその製造方法を提供する効果を有する。
Smart Images

Figure 0007634698000002 
Figure 0007634698000003 
Figure 0007634698000004
Abstract
Description
[Technical field]
[0001] The present invention relates to a thick polyimide unit film, a multilayer polyimide film containing the same, and a method for producing the same. [Background technology]
[0002] Recently, electronic devices have become lighter, smaller, thinner, and more highly integrated, which causes a lot of heat to be generated in the electronic devices. Such heat can shorten the lifespan of the product and can cause breakdowns and malfunctions. Therefore, thermal management for electronic devices has emerged as an important issue.
[0003] Graphite sheets have a higher thermal conductivity than metal sheets such as copper and aluminum, and are attracting attention as heat dissipation materials for electronic devices. In particular, research on thick graphite sheets, which have an advantage in terms of heat capacity compared to thin graphite sheets (e.g., graphite sheets with a thickness of about 40 μm or less), is actively being conducted.
[0004] Graphite sheets can be produced in a variety of ways, for example, by carbonizing and graphitizing a polymer film. In particular, polyimide films have been attracting attention as polymer films for producing graphite sheets due to their excellent mechanical, thermal, dimensional and chemical stability.
[0005] In order to manufacture a thick graphite sheet, a thick polyimide film (e.g., a polyimide film having a thickness of about 100 μm or more) must first be manufactured, but in the conventional method of manufacturing a polyimide film by casting a polyamic acid solution and heat treating it, it is difficult to uniformly harden the inside and outside, resulting in the generation of layer separation and air bubbles, making it difficult to manufacture a thick polyimide film. In addition, when manufacturing a thick polyimide film by bonding two or more polyimide films using an adhesive, there are problems such as layer separation due to heat resistance problems of the adhesive layer during the process in which the polyimide film is subjected to high temperatures for carbonization and graphitization, and the inability to manufacture a thick graphite sheet due to the lack of graphitization in the adhesive layer.
[0006] Alternatively, to manufacture a thick graphite sheet, two or more thin graphite sheets can be laminated using double-sided tape. However, in this case, there is a problem that the double-sided tape impedes heat diffusion, thereby reducing the thermal conductivity of the entire laminate of graphite sheets. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Republic of Korea Patent Publication No. 2017-0049912 Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a thick polyimide unit film and a multilayer polyimide film including the same.
[0009] Another object of the present invention is to provide a method for producing a multilayer polyimide film. [Means for solving the problem]
[0010] In order to achieve the above object, one embodiment of the present invention provides a method for adjusting the slope of an elastic deformation section by a plastic deformation method. The ratio of the slope of the plastic deformation zone (slope of the plastic deformation zone / slope of the elastic deformation zone) is 0.025 or less. A polyimide film is provided. (Note that the plastic deformation section corresponds to the section from an elongation of 30% to just before breakage in the stress-strain curve of the polyimide film, and the elastic deformation section corresponds to the section where the elongation is 3% or less.)
[0011] Another embodiment of the present invention is a polyimide core layer including the polyimide film, and an adhesive layer laminated on one or both sides of the polyimide core layer, The adhesive layer includes an imide group, The thickness is 50 μm or more. A polyimide unit film is provided.
[0012] Yet another embodiment of the present invention is a laminate produced by laminating two or more of the polyimide unit films. A multi-layer polyimide film is provided.
[0013] Yet another embodiment of the present invention is a method for manufacturing a polyimide unit film, comprising the steps of: forming two or more polyimide unit films each having an adhesive layer laminated on one or both sides of a polyimide core layer; laminating the two or more polyimide unit films so that they can be bonded to each other via the adhesive layer; and a step of thermally pressing the two or more laminated polyimide unit films together, The thickness of the polyimide unit film is 50 μm or more. A method for producing a multilayer polyimide film is provided. Effect of the Invention
[0014] The present invention has an effect of providing a thick polyimide unit film, a multilayer polyimide film containing the same, and a method for producing the same. [Brief description of the drawings]
[0015] [Figure 1] 1 is a graph showing a stress-strain curve (SS-curve) of a polyimide film according to a preparation example of the present invention, the graph showing a plastic deformation region and an elastic deformation region. [Diagram 2] 1 is a schematic diagram of a multilayer polyimide film according to an embodiment of the present invention. [Diagram 3] 1 is a schematic diagram of a multilayer polyimide film according to an embodiment of the present invention. [Figure 4] 1 is a photograph showing the results of plastic deformation of polyimide films of Production Examples 1 and 2 of the present invention and Comparative Production Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, the embodiments and examples of the present invention will be described in detail so that those skilled in the art can easily carry out the present invention. However, the present invention can be realized in various different forms and is not limited to the embodiments and examples described herein. Throughout this specification, when a part "includes" a certain element, this does not mean that other elements are excluded, but that other elements can be further included, unless otherwise specified.
[0017] In this specification, the singular expression includes the plural expression unless the context clearly indicates otherwise.
[0018] When interpreting elements, they are interpreted as including error ranges even if there is no explicit statement to the contrary.
[0019] In this specification, the "to" in the expression "a to b" indicating a numerical range is defined as ≧a and ≦b.
[0020] In the polyimide film according to one embodiment of the present invention, the ratio of the slope of the plastic deformation section to the slope of the elastic deformation section (slope of plastic deformation section / slope of elastic deformation section) may be 0.025 or less, preferably 0.023 or less.
[0021] The plastic deformation section corresponds to the section from an elongation of 30% to just before breakage in the stress-strain curve (SS-curve) of the polyimide film shown in FIG. 1, and the elastic deformation section corresponds to the section where the elongation is 3% or less.
[0022] On the other hand, the ratio of the slope of the plastic deformation section to the slope of the elastic deformation section of the polyimide film (slope of the plastic deformation section / slope of the elastic deformation section) may be 0.01 or more.
[0023] In one embodiment, the slope of the plastic deformation section of the polyimide film may be 0.05 GPa or less.
[0024] On the other hand, the gradient of the plastic deformation section of the polyimide film may be 0.020 GPa or more, preferably 0.027 GPa or more, and more preferably 0.030 GPa or more.
[0025] The polyimide film may have a gradient of 2.1 GPa or more in the elastic deformation section, and preferably has a gradient of 2.11 GPa or more in the elastic deformation section.
[0026] On the other hand, the gradient of the elastic deformation section of the polyimide film may be 3.0 GPa or less.
[0027] If the ratio of the plastic deformation section to the slope of the elastic deformation section of the polyimide film and / or the slope of the plastic deformation section of the polyimide film is above or below the above range, sintering (graphitization) to produce a graphite sheet is not easy.
[0028] In other words, a multilayer polyimide film produced by laminating polyimide unit films becomes very thick and is not easy to sinter (graphitize), making it difficult to produce a graphite sheet, so it is necessary to use a polyimide core layer that is as easy to sinter as possible.
[0029] In order to facilitate the baking, it is necessary to suppress the progress of imidization of the polyimide used as the core layer, and this can be achieved by adjusting the amount of heat during the production of the polyimide.
[0030] In one embodiment, the polyimide film may have a tensile strength of 200 MPa or less, preferably 195 MPa or less.
[0031] The polyimide film may have a tensile strength of 170 MPa or more.
[0032] This is because the tensile strength of the polyimide film is affected as a result of the adjustment of the amount of heat to facilitate baking, resulting in a decrease in the tensile strength.
[0033] The dianhydride monomer for producing the polyimide film of the present invention is pyromellitic dianhydride. Water, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 3,4,9,10-perylenetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)propane dianhydride Water, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)ethane dianhydride, oxydiphthalic dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, p-phenylene bis(trimellitic acid monoester anhydride), ethylene bis(trimellitic acid monoester anhydride), bisphenol A bis(trimellitic acid monoester anhydride), or derivatives thereof , or a combination thereof, and examples of the diamine monomer include 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-oxydianiline, 3,4'-oxydianiline, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenylpropane, 4,4'-methylenedianiline, 3,3'-methylene Dianiline, benzidine, 3,3'-dichlorobenzidine, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,5-diaminonaphthalene, 4,4'-diaminodiphenyl diethyl silane, 4,4'-diaminodiphenyl silane, 4,4'-diaminodiphenyl ethyl phosphine oxide, 4,4'-diaminodiphenyl N-methylamine, 4,4'-diaminodiphenyl N-phenylamine, 1,4-diaminobenzene (p-phenylenediamine), 1,3-diaminobenzene, 1,2-diaminobenzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, or derivatives thereof, or combinations thereof can be used.
[0034] A polyimide unit film according to another aspect of the present invention includes a polyimide core layer including the polyimide film, and an adhesive layer laminated on one or both sides of the polyimide core layer, the adhesive layer including an imide group, and the thickness of the polyimide unit film may be 50 μm or more.
[0035] For example, the polyimide unit film may have a thickness of, but is not limited to, 50 μm to 500 μm, as another example, 100 μm to 300 μm, and as yet another example, 125 μm to 250 μm.
[0036] In one embodiment, in the polyimide unit film, a ratio of a thickness of the polyimide core layer to a thickness of the adhesive layer may be 1:0.004 to 1:0.095.
[0037] That is, when the polyimide unit film has an adhesive layer laminated on only one surface of the polyimide core layer, the ratio of the thickness of the polyimide core layer to the thickness of the adhesive layer may be 1:0.004 to 1:0.095.
[0038] In addition, when the polyimide unit film has adhesive layers laminated on both sides of the polyimide core layer, the ratio of the thickness of the polyimide core layer to the thickness of the adhesive layers (the total thickness of the adhesive layers laminated on both sides) may be 1:0.008 to 1:0.19.
[0039] In one embodiment, the adhesive layer may have a glass transition temperature (Tg) of 300° C. or less, and the polyimide core layer may have a glass transition temperature (Tg) of 350° C. or more.
[0040] In particular, the polyimide core layer can comprise a non-thermoplastic polyimide and the adhesive layer can comprise a thermoplastic polyimide, and preferably, the polyimide core layer consists solely of a non-thermoplastic polyimide and the adhesive layer consists solely of a thermoplastic polyimide.
[0041] In one embodiment, the polyimide core layer and the adhesive layer are formed from a dianhydride monomer and a diamine monomer. For example, the polyimide core layer and the adhesive layer may be prepared by imidizing a polyamic acid formed by a reaction between a dianhydride monomer and a diamine monomer. The types of dianhydride monomers and diamine monomers that can be used to form the polyimide core layer and the adhesive layer may be the above-mentioned dianhydride monomers and diamine monomers, but are not limited thereto, and various monomers commonly used in the field of polyimide film manufacturing can be used.
[0042] For example, the polyimide core layer may be formed by reacting 100 mol% of pyromellitic dianhydride (PMDA) as a dianhydride monomer with 100 mol% of 4,4'oxydianiline (ODA) as a diamine monomer, and the adhesive layer may be formed by reacting 100 mol% of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) as a dianhydride monomer with 100 mol% of 4,4'oxydianiline (ODA) as a diamine monomer.
[0043] For example, the dianhydride monomer for forming the polyimide core layer and the adhesive layer may be pyromellitic dianhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 1,2,5,6-naphthalenetetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)propane dianhydride, 3,4,9,10-Perylenetetracarboxylic dianhydride, bis(3,4-dicarboxyphenyl)propane dianhydride, 1,1-bis(2,3-dicarboxyphenyl)ethane dianhydride, 1,1-bis(3,4-dicarboxyphenyl)ethane dianhydride, bis(2,3-dicarboxyphenyl)methane dianhydride, bis(3,4-dicarboxyphenyl)ethane dianhydride, oxydiphthalic dianhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, p-phenylenebis(trimellitic acid monoester acid anhydride), ethylenebis(trimellitic acid Monoester anhydride), bisphenol A bis(trimellitic acid monoester anhydride), or derivatives thereof, or combinations thereof; diamine monomers include 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-oxydianiline, 3,4'-oxydianiline, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, p-phenylenediamine, m-phenylenediamine, Diamine, 4,4'-diaminodiphenylpropane, 4,4'-methylenedianiline, 3,3'-methylenedianiline, benzidine, 3,3'-dichlorobenzidine, 4,4'-diaminodiphenyl sulfide, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl sulfone, 4,4'-diaminodiphenyl ether, 3,3'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 1,5-diaminonaphthalene, 4,4'-diaminodiphenyldiethylsilane, 4,4'-diaminodiphenylsilane, 4,4'-Diaminodiphenylethylphosphine oxide, 4,4'-diaminodiphenyl N-methylamine, 4,4'-diaminodiphenyl N-phenylamine, 1,4-diaminobenzene (p-phenyl, Nylenediamine), 1,3-diaminobenzene, 1,2-diaminobenzene, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, or derivatives thereof, or combinations thereof can be used.
[0044] In one embodiment, the dianhydride monomer for forming the non-thermoplastic polyimide core layer may be pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, oxydiphthalic anhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, or a combination thereof. The diamine monomer may be 4,4'-oxydianiline, 3,4'-oxydianiline, p-phenylenediamine, m-phenylenediamine, 4,4'-methylenedianiline, 3,3'-methylenedianiline, or a combination thereof. In this case, a polyimide layer with excellent orientation may be formed, and a graphite sheet having excellent thermal conductivity may be formed when carbonized and graphitized, but the present invention is not limited thereto.
[0045] In one embodiment, the dianhydride monomer for forming the thermoplastic polyimide adhesive layer may be 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, or a combination thereof. The diamine monomer may be 4,4'-oxydianiline, 3,4'-oxydianiline, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, or a combination thereof.
[0046] For example, the polyimide core layer may be formed by reacting 100 mol% of pyromellitic dianhydride (PMDA) as a dianhydride monomer with 100 mol% of 4,4'oxydianiline (ODA) as a diamine monomer, and the adhesive layer may be formed by reacting 100 mol% of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) as a dianhydride monomer with 100 mol% of 4,4'oxydianiline (ODA) as a diamine monomer.
[0047] In one embodiment, any known film lamination method can be used to produce the polyimide unit film.
[0048] For example, a coating method, a bonding sheet method, a co-extrusion method, etc. can be used. The coating method is a method in which an adhesive layer is formed to a certain thickness on a polyimide core layer prepared by a conventional method, and then dried to produce a polyimide unit film.
[0049] The bonding sheet method is a method of manufacturing a polyimide unit film by simultaneously putting a polyimide core film and a sheet-shaped adhesive layer film (bonding sheet) into a calendaring process.
[0050] The co-extrusion method is a method for producing a polyimide unit film by simultaneously forming an adhesive layer and a polyimide core layer using a co-extrusion die in a step of casting a polyamic acid solution on a metal support layer.
[0051] The multilayer polyimide film according to another embodiment of the present invention can be produced by laminating two or more of the polyimide unit films.
[0052] The thickness of the multilayer polyimide film can be easily controlled by adjusting the thickness (e.g., the thickness of the polyimide core layer, the thickness of the adhesive layer) and the number of polyimide unit films to be laminated. For example, to satisfy a predetermined thickness, the multilayer polyimide film can be formed by laminating two or more polyimide unit films (e.g., 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, or 15 or more), as another example, 2 to 1,000, as yet another example, 2 to 100, as yet another example, 2 to 50, and as yet another example, 2 to 10.
[0053] That is, the multilayer polyimide film includes two or more polyimide unit films each including a polyimide core layer and an adhesive layer laminated on one or both sides of the polyimide core layer, and in this case, the two or more polyimide unit films may be adhesively laminated via the adhesive layer.
[0054] For example, when the adhesive layer is a thermoplastic polyimide layer, it can be easily bonded by thermocompression bonding or the like, and has excellent adhesive strength.
[0055] In one embodiment, the multilayer polyimide film may have a thickness of 100 μm or more.
[0056] For example, the multilayer polyimide film may have a thickness of, but is not limited to, 100 μm to 20,000 μm, for another example, 150 μm to 2,000 μm, and for yet another example, 200 μm to 1,000 μm.
[0057] In one embodiment, the polyimide unit films included in the multilayer polyimide film may be the same or different from each other, for example, the polyimide core layer and / or adhesive layer materials (e.g., polyimide precursor components, component contents), thicknesses, etc. of the polyimide unit films may be the same or different from each other.
[0058] In addition, when the polyimide unit film has adhesive layers containing thermoplastic polyimide layers laminated on both sides of a polyimide core layer made of a non-thermoplastic polyimide, the thermoplastic polyimide layers in each adhesive layer may be the same or different from each other.
[0059] Furthermore, the non-thermoplastic polyimide layer and / or the thermoplastic polyimide layer contained in the polyimide unit film may be composed of a single layer or multiple layers.
[0060] In one embodiment, the thermoplastic polyimide layers included in each polyimide unit film may be made of the same material. In this case, the adhesive strength between the thermoplastic polyimide layers may be excellent and the peeling prevention effect during post-processing may be excellent, but is not limited thereto.
[0061] 2 is a schematic diagram of a multilayer polyimide film 100 according to an embodiment of the present invention. Referring to FIG. 2, the multilayer polyimide film 100 may include polyimide unit films 110 and 120 each including a polyimide core layer 111 and 121 and an adhesive layer 112 and 122 laminated on one side of the polyimide core layer 111 and 121, and may optionally further include one or more (e.g., 2, 3, 4, 5, 6, 7, 8, 9, or 10 or more) polyimide unit films (not shown) each including a polyimide core layer and an adhesive layer laminated on both sides of the polyimide core layer between the polyimide unit films 110 and 120.
[0062] For example, a multi-layer polyimide film may include a polyimide core layer and a polyimide core layer. and one or more second polyimide unit films each including a polyimide core layer and an adhesive layer laminated on both sides of the polyimide core layer, wherein the one or more second polyimide unit films are interposed between the two first polyimide unit films, and the first polyimide unit film and the second polyimide unit film are adhesively laminated via an adhesive layer included in the first polyimide unit film and the second polyimide unit film.
[0063] 3 is a schematic diagram showing a multilayer polyimide film 200 according to another embodiment of the present invention. Referring to FIG. 3, the multilayer polyimide film 200 may include polyimide unit films 210 and 220 each including a polyimide core layer 211 and 221 and an adhesive layer 212 and 222 laminated on both sides of the polyimide core layer 211 and 221, and may optionally further include one or more (e.g., 2, 3, 4, 5, 6, 7, 8, 9, or 10 or more) polyimide unit films (not shown) each including a polyimide core layer and an adhesive layer on both sides of the polyimide core layer between the polyimide unit films 210 and 220.
[0064] In one embodiment, the adhesive strength between the laminated polyimide unit films of the multilayer polyimide film may be 0.3 kgf / cm or more, for example, 0.5 kgf / cm or more, and as another example, 0.6 kgf / cm or more.
[0065] On the other hand, the adhesive strength between the laminated polyimide unit films of the multilayer polyimide film may be 1.5 kgf / cm or less.
[0066] In one embodiment, when the multilayer polyimide film is heated at 600° C. or more for one hour or less, no interlayer separation occurs between the laminated polyimide unit films. For example, the heating time for which no interlayer separation occurs may be 50 minutes or less, and as another example, 30 minutes or less.
[0067] The temperature at which no interlayer separation occurs between the laminated polyimide unit films may be, for example, 650° C. or higher, or as another example, 700° C. or higher.
[0068] On the other hand, the temperature at which no interlayer separation occurs between the laminated polyimide unit films may be 3,000° C. or lower.
[0069] In one embodiment, the multilayer polyimide film may be for use in producing graphite sheets.
[0070] The multilayer polyimide film has excellent adhesive strength between polyimide unit films, and when the multilayer polyimide film is carbonized and graphitized, a thick graphite sheet having excellent thermal conductivity can be produced without layer separation at the adhesive interface.
[0071] When the multilayer polyimide film is used for producing a graphite sheet, the polyimide unit film may further include an inorganic filler, preferably a sublimable inorganic filler.
[0072] Here, the term "sublimable inorganic filler" may refer to an inorganic filler that is sublimated by heat during the carbonization and / or graphitization process in the manufacture of a graphite sheet. When the polyimide film contains a sublimable inorganic filler, voids are formed in the graphite sheet by gas generated by sublimation of the sublimable inorganic filler in the manufacture of the graphite sheet, and thus the sublimation gas generated in the manufacture of the graphite sheet can be smoothly exhausted, resulting in a high-quality graphite sheet. Not only can the graphite sheet be obtained, but the flexibility of the graphite sheet can be improved, ultimately improving the handleability and moldability of the graphite sheet. Examples of the sublimable inorganic filler include, but are not limited to, calcium carbonate, dibasic calcium phosphate, barium sulfate, etc.
[0073] Average particle size of sublimable inorganic filler (D 50) may be 0.05 μm to 5.0 μm (for example, 0.1 μm to 4.0 μm), and a graphite sheet of good quality can be obtained within the above range, but is not limited to this.
[0074] The content of the sublimable inorganic filler may be 0.001 to 0.5 parts by weight based on 100 parts by weight of the polyimide film, and a graphite sheet of good quality can be obtained within the above range, but is not limited thereto.
[0075] In one embodiment, both the polyimide core layer and the adhesive layer in the polyimide unit film contain a sublimable inorganic filler. In another embodiment, the adhesive layer may contain a sublimable inorganic filler and the polyimide core layer may not contain a sublimable inorganic filler, or vice versa.
[0076] According to still another aspect of the present invention, a method for producing a multilayer polyimide film may include the steps of forming two or more polyimide unit films having an adhesive layer laminated and integrated on one or both sides of a polyimide core layer, laminating the two or more polyimide unit films so that they can be adhered via the adhesive layer, and thermocompressing the two or more laminated polyimide unit films, wherein the polyimide unit films have a thickness of 50 μm or more, and the polyimide core layer may include the polyimide film.
[0077] First, a polyimide unit film can be formed by laminating an adhesive layer integrally on one or both sides of a polyimide core layer using a known film lamination method.
[0078] The polyimide unit film can be produced, for example, by preparing a non-thermoplastic polyimide layer precursor composition as a polyimide core layer, preparing a thermoplastic polyimide layer precursor composition as an adhesive layer, forming the non-thermoplastic polyimide layer precursor composition and the thermoplastic polyimide layer precursor composition into a film shape of two or more layers on a support, drying the composition to form a gel film, and heat-treating the gel film.
[0079] The non-thermoplastic polyimide layer precursor composition may be prepared by, for example, mixing a solvent, a diamine monomer, and a dianhydride monomer to form a polyamic acid solution, and may optionally further include a step of adding a sublimable inorganic filler, a dehydrating agent, and / or an imidizing agent to the polyamic acid solution. The thermoplastic polyimide layer precursor composition may be prepared by, for example, mixing a solvent, a diamine monomer, and a dianhydride monomer to form a polyamic acid solution, and may optionally further include a step of adding a sublimable inorganic filler, a dehydrating agent, and / or an imidizing agent to the polyamic acid solution. The diamine monomer, the dianhydride monomer, and the sublimable inorganic filler are described above.
[0080] The solvent is not particularly limited as long as it can dissolve the polyamic acid. For example, the solvent can include an aprotic polar solvent. Examples of the aprotic polar solvent include amide-based solvents such as N,N'-dimethylformamide (DMF) and N,N'-dimethylacetamide (DMAc), phenol-based solvents such as p-chlorophenol and o-chlorophenol, N-methyl-pyrrolidone (NMP), gamma-butyrolactone (GBL), diglyme, etc. These can be used alone or in combination of two or more. In some cases, the solubility of the polyamic acid can be adjusted by using an auxiliary solvent such as toluene, tetrahydrofuran (THF), acetone, methyl ethyl ketone (MEK), methanol, ethanol, or water.
[0081] According to one embodiment, the polyamic acid solution may have a solid content, i.e., the weight percentage of the diamine monomer and the dianhydride monomer relative to the total weight of the diamine monomer, the dianhydride monomer, and the solvent, of, for example, 5 to 35 wt %, and another example, 10 to 30 wt %. Within this range, the polyamic acid solution may have a molecular weight and viscosity suitable for forming a film, but is not limited thereto.
[0082] According to one embodiment, the polyamic acid solution for forming a non-thermoplastic polyimide layer may have a viscosity of 100,000 cP to 500,000 cP at 23°C. In this range, the polyamic acid can have a predetermined molecular weight while being excellent in processability during polyimide film formation. Here, the "viscosity" can be measured using a HAAKE Mars viscometer. For example, the viscosity of the polyamic acid solution may be 150,000 cP to 450,000 cP at 23°C, as another example, 200,000 cP to 400,000 cP, and as yet another example, 220,000 cP to 350,000 cP, but is not limited thereto.
[0083] According to one embodiment, the polyamic acid solution for forming a thermoplastic polyimide layer may have a viscosity of 1,000 cP to 500,000 cP at 23°C. In the above range, the polyamic acid has a predetermined molecular weight, and is excellent in processability during polyimide film formation and can be thermocompressed under appropriate temperature and pressure. Here, the "viscosity" can be measured using a HAAKE Mars viscometer. For example, the viscosity of the polyamic acid solution may be 1,000 cP to 100,000 cP at 23°C, as another example, 1,000 cP to 50,000 cP, and as yet another example, 5,000 cP to 50,000 cP, but is not limited thereto.
[0084] According to one embodiment, the polyamic acid for forming the non-thermoplastic polyimide layer may have a weight average molecular weight of 50,000 g / mol to 500,000 g / mol. This range may be advantageous for producing a graphite sheet having better thermal conductivity. Here, the "weight average molecular weight" may be measured using gel permeation chromatography (GPC) with polystyrene as a standard sample. For example, the weight average molecular weight of the polyamic acid may be 150,000 g / mol to 500,000 g / mol, or another example, 100,000 g / mol to 400,000 g / mol, but is not limited thereto.
[0085] According to one embodiment, the polyamic acid for forming the thermoplastic polyimide layer may have a weight average molecular weight of 5,000 g / mol to 500,000 g / mol, but is not limited thereto. This range may be advantageous for producing a graphite sheet having better thermal conductivity. Here, the "weight average molecular weight" can be measured by gel permeation chromatography (GPC) using polystyrene as a standard sample.
[0086] The dehydrating agent promotes the ring-closing reaction by dehydrating the polyamic acid. Examples of the dehydrating agent include aliphatic acid anhydrides, aromatic acid anhydrides, N,N'-dialkylcarbodiimides, halogenated lower aliphatic halides, halogenated lower fatty acid anhydrides, allylphosphonic acid dihalides, and thionyl halides. These can be used alone or in combination of two or more. Among these, from the viewpoint of availability and cost, aliphatic acid anhydrides such as acetic anhydride, propionic anhydride, and lactic anhydride can be used alone or in combination of two or more. The dehydrating agent is used in an amount of 0.5 to 5 moles per mole of amic acid groups in the polyamic acid. The amount of the copolymer added is not limited to 1 mole (for example, 1 mole to 4 moles). Within this range, sufficient imidization is possible and it may be advantageous for casting into a film.
[0087] The imidizing agent is an agent that promotes a ring-closing reaction with polyamic acid, and examples thereof include aliphatic tertiary amines, aromatic tertiary amines, and heterocyclic tertiary amines. Among them, heterocyclic tertiary amines can be used from the viewpoint of reactivity as a catalyst. Examples of heterocyclic tertiary amines include quinoline, isoquinoline, β-picoline, pyridine, and the like, which can be used alone or in combination of two or more. The imidizing agent is added in an amount of 0.05 mol to 3 mol (for example, 0.2 mol to 2 mol) per mol of amic acid group in polyamic acid, and sufficient imidization is possible within the above range, which may be advantageous for casting into a film, but is not limited thereto.
[0088] Thereafter, the non-thermoplastic polyimide layer precursor composition and the thermoplastic polyimide layer precursor composition can be formed into a film shape of two or more layers on a support and dried to form a gel film.
[0089] Any known manufacturing method can be applied to manufacture a film having two or more layers, such as a coating method, a bonding sheet method, a co-extrusion method, and the like.
[0090] In particular, when the composition is produced by coextrusion, a non-thermoplastic polyimide layer precursor composition and a thermoplastic polyimide layer precursor composition are simultaneously fed to an extruder having a die for extrusion molding of two or more layers, and the two compositions are coextruded from the outlet of the die into a film shape of two or more layers, and then dried to produce a gel film.
[0091] More specifically, a non-thermoplastic polyimide layer precursor composition and a thermoplastic polyimide layer precursor composition are simultaneously supplied to a two or more layer molding die, and the two compositions discharged from the two or more layer extrusion molding die are continuously formed into a film shape on a support, and then heated and dried (for example, at 30°C to 300°C) to produce a gel film having self-supporting properties, and the gel film is separated from the support and then treated at a high temperature (for example, at 50°C to 700°C) to obtain a polyimide film. As the two or more layer molding die, various known structures can be used, and for example, a T die for producing a multilayer film (for example, a feed block T die or a multi-manifold T die) can be used.
[0092] According to one embodiment, the non-thermoplastic polyimide layer and the thermoplastic polyimide layer of the polyimide unit film may be in direct contact with each other, where "direct contact" may mean that no other layer is interposed between the non-thermoplastic polyimide layer and the thermoplastic polyimide layer.
[0093] Examples of the support include a glass plate, an aluminum foil, an endless stainless steel belt, and a stainless steel drum. Drying is performed at a temperature of, for example, but not limited to, 30°C to 300°C (e.g., 80°C to 200°C, as another example, 100°C to 180°C, and as yet another example, 100°C to 150°C). Drying time is, for example, but not limited to, 1 minute to 10 minutes, as another example, 2 minutes to 7 minutes, and as yet another example, 2 minutes to 5 minutes.
[0094] In some cases, in order to adjust the thickness and size of the final polyimide unit film and improve the orientation, a step of stretching the gel film may be included, and the stretching is performed in at least one direction of MD (machine direction) and TD (transverse direction). In order to achieve smooth orientation of the polymer, the heating must be performed at a low temperature of less than 50° C. Because at temperatures above 50° C., the imidization reaction is promoted, which hinders the orientation of the polymer.
[0095] Thereafter, the gel film is heat-treated to produce a polyimide unit film. By heat-treating the gel film, most of the amic acid groups remaining in the gel film are imidized to obtain a polyimide film. The heat treatment temperature may be, but is not limited to, 50°C to 700°C, for example, 150°C to 600°C, as another example, 200°C to 600°C, as yet another example, 350°C to 500°C, and as yet another example, 400°C to 450°C. The heat treatment time is, but is not limited to, for example, 1 minute to 20 minutes, as another example, 1 minute to 10 minutes, and as yet another example, 2 minutes to 8 minutes.
[0096] Next, two or more polyimide unit films can be laminated so as to be bonded to each other via an adhesive layer (e.g., a thermoplastic polyimide layer). More specifically, the polyimide unit films can be laminated so that the adhesive layers face each other.
[0097] Next, the two or more laminated polyimide unit films can be thermocompression bonded, for example, at a pressure of 0.1 MPa to 30 MPa and a temperature of 250° C. to 450° C. for 10 seconds to 150 seconds, but is not limited thereto.
[0098] According to one embodiment, the thermoplastic polyimide layers of the polyimide unit films (for example, in the case where two polyimide unit films are included, the thermoplastic polyimide layer of one polyimide unit film and the thermoplastic polyimide layer of the other polyimide unit film) may be in direct contact with each other.
[0099] In the multilayer polyimide film produced as described above, two or more polyimide unit films each having an adhesive layer laminated and integrated on one or both sides of a polyimide core layer are heat-pressurized to be laminated via the adhesive layer, so that the polyimide unit films can be bonded with excellent adhesive strength.
[0100] Such excellent adhesion can be converted into a thick graphite sheet with excellent thermal conductivity without layer separation at the adhesive interface when the multilayer polyimide film is carbonized and / or graphitized for use as a graphite sheet.
[0101] According to yet another aspect of the present invention, there is provided a graphite sheet manufactured from the multilayer polyimide film described above or the multilayer polyimide film manufactured by the manufacturing method described above. The graphite sheet has a thickness of 50 μm or more, for example, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm or 200 μm or more, for example, 50 μm to 4,000 μm, and for example, 50 μm to 500 μm, and yet has excellent thermal conductivity.
[0102] According to one embodiment, the graphite sheet may have a thermal conductivity of 500 W / m·K or more (e.g., 500 W / m·K, 600 W / m·K, 700 W / m·K, 800 W / m·K, 900 W / m·K, 1,000 W / m·K, 1,100 W / m·K, 1,200 W / m·K, 1,300 W / m·K, 1,400 W / m·K, or 1,500 W / m·K or more). For example, the thermal conductivity of the graphite sheet may be 500 W / m·K to 2,000 W / m·K, or as another example, 1,000 W / m·K to 2,000 W / m·K, but is not limited thereto.
[0103] The graphite sheet described above can be manufactured by various methods commonly used in the field of graphite sheet manufacturing. For example, the graphite sheet can be manufactured by arranging the graphite sheet on the multi-layer polyimide film described above. It can be produced by carbonizing and graphitizing.
[0104] "Carbonization" is a process of pyrolyzing the polymer chains of a polyimide film to form a preliminary graphite sheet containing an amorphous carbon body, a non-crystalline carbon body, and / or an amorphous carbon body, and may include, but is not limited to, a step of heating and maintaining the temperature of the polyimide film from room temperature to a maximum temperature in the range of 1,000°C to 1,500°C under reduced pressure or in an inert gas atmosphere for 10 to 30 hours. Optionally, in order to achieve high carbon orientation, pressure may be applied to the polyimide film during carbonization using a hot press or the like, and the pressure may be, for example, 5 kg / cm. 2 The above is another example of 15kg / cm 2 The above is another example of 25kg / cm 2 It may be more than this, but is not limited to this.
[0105] Graphitization is a process of forming a graphite sheet by rearranging carbon in an amorphous carbon body, non-crystalline carbon body, and / or amorphous carbon body, and may include, but is not limited to, a step of heating and maintaining a temperature of a preliminary graphite sheet from room temperature to a maximum temperature in the range of 2,500°C to 3,000°C in an inert gas atmosphere for 2 hours to 30 hours. Optionally, in order to achieve high carbon orientation, pressure may be applied to the preliminary graphite sheet during graphitization using a hot press or the like, and the pressure may be, for example, 100 kg / cm. 2 The above is another example of 200kg / cm 2 The above, and further examples of 300 kg / cm 2 It may be more than this, but is not limited to this. EXAMPLES
[0106] The present invention will be described in more detail below with reference to examples. However, these are presented as preferred examples of the present invention and should not be construed as limiting the present invention in any way.
[0107] Manufacturing Example 205.0 g of dimethylformamide was added as a solvent to a reactor, and the temperature was adjusted to 20°C. 21.5 g of 4,4'-oxydianiline (ODA) was added as a diamine monomer, and then 23.4 g of pyromellitic dianhydride (PMDA) was added as a dianhydride monomer to prepare a polyamic acid solution with a viscosity of 230,000 cP. Next, 39.5 g of acetic anhydride as a dehydrating agent, 4.8 g of β-picoline as an imidizing agent, and dibasic calcium phosphate (average particle size (D 50 0.12 g of 2.5 μm xylene and 30.4 g of dimethylformamide as a solvent were mixed to prepare a non-thermoplastic polyimide precursor solution.
[0108] The non-thermoplastic polyimide precursor solution prepared in the film-forming device was cast on a SUS plate (100SA, Sandvik) and dried to produce a gel film. The gel film produced was separated from the SUS plate and then heat-treated to produce a polyimide film.
[0109] During the heat treatment, the amount of heat was adjusted so that the maximum temperature during the heat treatment was 510°C in Preparation Example 1, 520°C in Preparation Example 2, and 550°C in Preparation Comparative Example 1, to produce polyimide films of Preparation Examples 1 and 2 and Preparation Comparative Example 1.
[0110] The polyimide films of Production Examples 1 and 2 and Production Comparative Example 1 were subjected to measurement of tensile properties according to ASTM D882. The results were shown in a stress-strain curve with the tensile strength (MPa) on the vertical axis and the deformation rate (%) on the horizontal axis. As shown in Table 1 below, the slope of the plastic deformation region and the slope of the elastic deformation region were measured, and then the ratio between them was calculated.
[0111] The plastic deformation section corresponds to the stress-strain curve (st The elastic deformation section corresponds to the section from an elongation of 30% to just before fracture in a stress-strain curve (SS-curve), and the elastic deformation section corresponds to the section in which the deformation rate is 3% or less.
[0112] The slope of each section was derived by calculating the amount of change in tensile strength / the amount of change in deformation rate in each section. At this time, for example, the deformation rate of 3% was changed to 0.03 for the calculation.
[0113] [Table 1]
[0114] The polyimide films of Production Examples 1 and 2 corresponded to the ratio of the slope of the plastic deformation section to the slope of the elastic deformation section (slope of the plastic deformation section / slope of the elastic deformation section) and the range of the slope of the plastic deformation section of the present application, but the ratio of the slope of the plastic deformation section to the slope of the elastic deformation section (slope of the plastic deformation section / slope of the elastic deformation section) and the range of the slope of the plastic deformation section of Production Comparative Example 1 were outside of the range of the present application. In addition, the tensile strengths of the polyimide films of Production Examples 1 and 2 were 180 MPa and 191 MPa, respectively, both of which corresponded to 200 MPa or less.
[0115] Meanwhile, the tensile strength of the polyimide film of Comparative Preparation 1 was measured to be about 210 MPa. The polyimide films of Comparative Preparation 1 and Comparative Preparation 1 were heated to 1,200°C at an average rate of 0.5°C / min in an argon gas atmosphere using an electric furnace, and were maintained at the same temperature for 3 hours to allow carbonization to proceed, and were then heated again to 2,800°C at an average rate of 1.0°C / min in an argon gas atmosphere, and were maintained at the same temperature for 1 hour to allow graphitization to proceed.
[0116] As shown in FIG. 4, the polyimide films of Preparation Examples 1 and 2 had no problems with graphitization (FIGS. 4a and 4b, respectively). However, it was confirmed that the polyimide film of Comparative Preparation Example 1, which was outside the range of the slope of the plastic deformation region and the slope of the plastic deformation region / slope of the elastic deformation region of the present application, was excessively imidized, was not easily sintered, and was not successfully graphitized (FIG. 4c).
[0117] Examples and Experiments Example 1 A non-thermoplastic polyimide precursor solution (used as a polyimide core layer) was prepared in the same manner as in the above-mentioned preparation example.
[0118] In a separate reactor, 217.5 g of dimethylformamide was added as a solvent and the temperature was adjusted to 20°C. 13.2 g of 4,4'oxydianiline (ODA) was added as a diamine monomer, and then 19.3 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) was added as a dianhydride monomer to prepare a polyamic acid solution with a viscosity of 10,000 cP. Next, 23.2 g of acetic anhydride was added as a dehydrating agent, 3.0 g of β-picoline was added as an imidizing agent, and 2-calcium phosphate (average particle size (D 50 0.09 g of ethylenediaminetetraacetate (1.5 μm) and 18.6 g of dimethylformamide as a solvent were mixed to prepare a precursor solution for the adhesive layer (thermoplastic polyimide layer).
[0119] The produced precursor solution for non-thermoplastic polyimide layer and the precursor solution for thermoplastic polyimide layer were formed on a SUS plate (100SA, Sandvik) using a film-forming device equipped with a three-layer extrusion die so that the thermoplastic polyimide layers were laminated and integrated on both sides of the non-thermoplastic polyimide layer, and the film was dried at 130°C for 3 minutes to produce a gel film. The produced gel film was separated from the SUS plate and then heat-treated at 420 to 550°C for 4 minutes to produce a polyimide unit film with a thermoplastic polyimide layer / non-thermoplastic polyimide layer / thermoplastic polyimide layer (thickness: 3 μm / 46 μm / 3 μm) structure.
[0120] Four sheets of the prepared polyimide unit films were laminated and then heat-pressed at 350° C. for 1 minute while applying a pressure of 20 MPa to prepare a multi-layer polyimide film having a thickness of 202 μm.
[0121] Experimental Example 1 The adhesive strength between polyimide unit films was measured using the multilayer polyimide film test piece prepared in Example 1. The adhesive strength was measured by preparing a test piece with a width of 10 mm and a length of 100 mm, and peeling one side at a 90° angle at a speed of 25 mm / min.
[0122] The average adhesive strength between the laminated polyimide unit films was measured to be 0.63 kgf / cm.
[0123] Experimental Example 2 The glass transition temperature (Tg) was measured for each of the polyimide core layer and adhesive layer of the polyimide unit film of Example 1. The glass transition temperature was measured by determining the loss modulus and storage modulus of each layer using DMA, and the inflection point in the tangent graph of these was taken as the glass transition temperature.
[0124] As a result of the measurement, the glass transition temperature of the polyimide core layer was 395°C, and the glass transition temperature of the adhesive layer was 280°C.
[0125] Experimental Example 3 A multilayer polyimide film specimen prepared in Example 1 was heated in a heating furnace at 700° C. for 30 minutes, and then the presence or absence of interlayer separation was examined by SEM, but no interlayer separation was observed.
[0126] Example 2 The multilayer polyimide film of Example 1 was carbonized by heating it to 1,200°C at a rate of 1°C / min under nitrogen gas using an electric furnace and maintaining it at that temperature for 2 hours. Thereafter, the film was graphitized by heating it to 2,800°C at a rate of 20°C / min under argon gas and maintaining it at that temperature for 1 hour, and then passed between upper and lower metal rolls at room temperature to produce a graphite sheet having a thickness of 100 μm.
[0127] Experimental Example 4 The graphite sheet of Example 2 was cut into a circle with a diameter of 25.4 mm to prepare a test piece, and the thermal diffusivity of the test piece was measured by the laser flash method using a thermal diffusivity measuring device (LFA467, Netsch), and the thermal conductivity was calculated by multiplying the measured thermal diffusivity by the density and specific heat (theoretical value: 0.85 kJ / kg K). As a result, it was confirmed that the graphite sheet of Example 2 had an excellent thermal conductivity of 1,030 W / m K.
[0128] The embodiments of the manufacturing method of the present invention are described below by those skilled in the art. The above-mentioned embodiments are merely preferred embodiments that allow a person skilled in the art to easily carry out the present invention, and are not limited to the above-mentioned embodiments, and therefore the scope of the present invention is not limited thereto. Therefore, the true technical scope of the present invention must be determined by the technical ideas of the appended claims. In addition, it is obvious to those skilled in the art that various substitutions, modifications and changes are possible within the scope of the technical ideas of the present invention, and it is obvious that the parts that can be easily modified by those skilled in the art are also included in the scope of the present invention. [Industrial Applicability]
[0129] The present invention has an effect of providing a thick polyimide unit film, a multilayer polyimide film containing the same, and a method for producing the same.
Claims
1. A polyimide comprising a dianhydride monomer and a diamine monomer as polymerization units, The dianhydride monomer is composed of pyromellitic dianhydride (PMDA), The diamine monomer consists of 4,4'-oxydianiline (PDA); The ratio of the slope of the plastic deformation section to the slope of the elastic deformation section (slope of the plastic deformation section / slope of the elastic deformation section) is 0.025 or less. Polyimide film. (Note that the plastic deformation section corresponds to a section from an elongation of 30% to just before breakage in the stress-strain curve of the polyimide film, and the elastic deformation section corresponds to a section in which the elongation is 3% or less.)
2. The slope of the plastic deformation section is 0.05 GPa or less. The polyimide film according to claim 1 .
3. The slope of the elastic deformation section is 2.1 GPa or more. The polyimide film according to claim 1 .
4. The tensile strength is 200 MPa or less. The polyimide film according to claim 1 .
5. A polyimide core layer comprising a polyimide film; and an adhesive layer laminated on one or both sides of the polyimide core layer, The polyimide film has a ratio of the slope of the plastic deformation section to the slope of the elastic deformation section (slope of the plastic deformation section / slope of the elastic deformation section) of 0.025 or less. The adhesive layer includes an imide group, The thickness is 50 μm or more, The ratio of the thickness of the polyimide core layer to the thickness of the adhesive layer (thickness of the polyimide core layer:thickness of the adhesive layer) The ratio of s to s is 1:0.004 to 1:0.
095. Polyimide unit film. (Note that the plastic deformation section corresponds to a section from an elongation of 30% to just before breakage in the stress-strain curve of the polyimide film, and the elastic deformation section corresponds to a section in which the elongation is 3% or less.)
6. The adhesive layer has a glass transition temperature (Tg) of 300° C. or less, The polyimide core layer has a glass transition temperature (Tg) of 350° C. or higher; the polyimide core layer comprises a non-thermoplastic polyimide; The adhesive layer comprises a thermoplastic polyimide. The polyimide unit film according to claim 5 .
7. The polyimide core layer comprises a dianhydride monomer comprising pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, oxydiphthalic anhydride, bis(3,4-dicarboxyphenyl)sulfone dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, or a combination thereof; formed from diamine monomers including 4,4'-oxydianiline, 3,4'-oxydianiline, p-phenylenediamine, m-phenylenediamine, 4,4'-methylenedianiline, 3,3'-methylenedianiline, or combinations thereof; The polyimide unit film according to claim 5 .
8. The adhesive layer comprises a dianhydride monomer including 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3,3',4-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, or a combination thereof; formed from diamine monomers including 4,4'-oxydianiline, 3,4'-oxydianiline, 1,3-bis(4-aminophenoxy)benzene, 1,4-bis(4-aminophenoxy)benzene, 1,3-bis(3-aminophenoxy)benzene, 1,4-bis(3-aminophenoxy)benzene, or combinations thereof; The polyimide unit film according to claim 5 .
9. Produced by laminating two or more polyimide unit films according to any one of claims 5 to 8. Multi-layer polyimide film.
10. The adhesive strength between the laminated polyimide unit films is 0.3 kgf / cm or more. The multilayer polyimide film according to claim 9.
11. When heated at 600°C or higher for 1 hour or less, no interlayer separation occurs between the laminated polyimide unit films; The multilayer polyimide film according to claim 9.
12. For graphite sheet manufacturing, The multilayer polyimide film according to claim 9.
13. forming two or more polyimide unit films each having an adhesive layer laminated on one or both sides of a polyimide core layer; The two or more polyimide unit films are laminated so as to be bonded to each other via the adhesive layer. and and a step of thermally pressing the two or more laminated polyimide unit films together, The thickness of the polyimide unit film is 50 μm or more, the polyimide core layer includes a polyimide film having a ratio of a slope of a plastic deformation section to a slope of an elastic deformation section (slope of the plastic deformation section / slope of the elastic deformation section) of 0.025 or less (wherein the plastic deformation section corresponds to a section from an elongation of 30% to just before breakage in a stress-strain curve of the polyimide film, and the elastic deformation section corresponds to a section in which the elongation is 3% or less); A method for producing a multilayer polyimide film.
Citation Information
Patent Citations
Adhesive polyimide film
JP1999166162A
Polyimide molded body, and its manufacturing method
JP2008094015A
Graphite sheet polyimide film and production method thereof
JP2016017169A
Laminated film
JP2017114098A
Polyimide film
JP2017179148A